LEARNING TO EXPRESS GRATITUDE IN MANDARIN CHINESE THROUGH WEB-BASED INSTRUCTION - Yang, Li (My University, 2017)
This study explored the effectiveness of a self-access website as a tool to teach expressions of gratitude to learners of Mandarin Chinese. The web-based instruction included explicit instruction on how to express gratitude appropriately in Mandarin and various consciousness-raising exercises/activities. Two groups of learners who differed in their proficiency in Chinese received instruction for five weeks. The findings indicated that the instruction positively affected the metapragmatic assessment and pragmatic awareness of the learners at two different proficiency levels. In their reflective e-journals, learners also reported the benefits the website provided for their pragmatics learning. Based on the findings, this study proposed implications for the teaching of pragmatics.
Citation: Yang, L. (2016). LEARNING TO EXPRESS GRATITUDE IN MANDARIN CHINESE THROUGH WEB-BASED INSTRUCTION. Language Learning & Technology, 20(1), 191-208. Retrieved from <Go to ISI>://WOS:000376498900013
Keywords: Web-Based Instruction; Computer-Assisted Language Learning; Second; Language Acquisition; Education & Educational Research; Linguistics